ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI LUAS PENGUNGKAPAN SUKARELA MODAL INTELEKTUAL - Husna, Asmaul; Kamal, Maulana (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2022)
This study aims to analyze and obtain empirical evidence regarding the effect of audit committee size, concentration of share ownership, research and development, company age, and foreign ownership on voluntary disclosure of intellectual capital in mining companies. The sample in this study is a mining company listed on the Indonesia Stock Exchange in 2017-2019 which was selected using the purposive sampling method. Based on this method, a sample of 13 companies with 39 financial statements was obtained for analysis The analysis used includes classical assumption test, multiple linear analysis and hypothesis testing. The results of this study indicate that simultaneously and partially the variables of audit committee size, concentration of share ownership, research and development, company age, and foreign ownership have a significant effect on the extent of voluntary disclosure of intellectual capital